Gasified Grass and Wood Biochars Facilitate Plant Establishment in Acid Mine Soils. Issue 3 (1st May 2016) - Phillips, Claire L.; Trippe, Kristin M.; Whittaker, Gerald; Griffith, Stephen M.; Johnson, Mark G.; Banowetz, Gary M.
Abstract : Heavy metals in exposed mine tailings threaten ecosystems that surround thousands of abandoned mines in the United States. Biochars derived from the pyrolysis or gasification of biomass may serve as a valuable soil amendment to revegetate mine sites. We evaluated the ability of two biochars, produced by gasification of either Kentucky bluegrass seed screenings (KB) or mixed conifer wood (CW), to support the growth of plants in mine spoils from the abandoned Formosa and Almeda Mines in Oregon. To evaluate the potential for plant establishment in mine tailings, wheat was grown in tailings amended with biochar at rates ranging from 0 to 9% (w/w). Both KB and CW biochars promoted plant establishment by increasing soil pH, increasing concentrations of macro‐ and micronutrients, and decreasing the solubility and plant uptake of heavy metals. Formosa tailings required at least 4% biochar and Almeda soil required at least 2% biochar to promote healthy wheat growth. A complimentary experiment in which mine spoils were leached with simulated precipitation indicated that biochar amendment rates ≥4% were sufficient to neutralize the elution pH and reduce concentrations of potentially toxic elements (Zn, Cu, Ni, Al) to levels near or below concern. These findings support the use of gasified biochar amendments to revegetate acid mine soils. Core Ideas: Gasified biochars facilitated wheat growth in two mine spoil soils. Biochars increased pH, moisture, and nutrients and reduced soluble heavy metals. Gasified biochars have properties that may aid revegetation of mine spoils.